The Macroeconomic Policy Challenges of Balance Sheet Recession: Lessons from Japan for the European Crisis - Gunther Schnabl (Center for Economic Studies and ifo Institute (CESifo), 2013)
The paper compares the boom-and-bust cycles in Japan and Europe with respect to the reasons for excessive booms, the characteristics of the crises, and the (potential) effects of the crisis therapies. As in Japan the consequence of expansionary monetary and fiscal policies is the hysteresis of the low-interest rate and high government debt environment, the erosion of the allocation and signaling function of the interest rate, the gradual quasi-nationalization of financial institutions as well as gradual real income losses, the economic policy implication for Japan and Europe is the timely exit from the current crisis therapies.
Keywords: E32; E42; E58; 330; Japan; Europe; bubble economy; European crisis; low interest rate policy; government debt sustainability; balance sheet recession